Exploring the diverse acetylcholinesterase inhibitory potential of girinimbine: insights from in vitro assays, molecular docking, and simulation studies: Girinimbine’s acetylcholinesterase inhibitory potential - Taha, Manal Mohamed Elhassan; khalid, Asaad; Elfatih, Fatima; Mohan, Syam; Sukumaran, Sri Devi; Ul-Haq, Zaheer; Aljahdali, Ieman A.; Oraibi, Omar; Oraibi, Bassem; Alfaifi, Hassan Ahmad; Alzahrani, Amal Hamdan; Farasani, Abdullah; et al. (Cellular and Molecular Biology, 2024)
The search for new treatments for Alzheimer’s disease (AD) has led to the exploration of plant-based drugs as potential options. Acetylcholinesterase (AChE) inhibitors are widely used as anti-AD medications. This study aimed to investigate the inhibitory mechanism of girinimbine, a constituent of Murraya koenigii, on AChE. AChE inhibition was assessed by in vitro experiments using the modified Ellman method, as well as in silico molecular docking and molecular dynamic simulation. The results were compared to those of the well-known anti-AChE agents tacrine and propidium iodide. Girinimbine, propidium, and tacrine at concentrations of 3.8X10-5M, 1.1x10-5M, and 6.1x10-7M showed percentages of inhibition percentages of 35.6%, 28.2%, and 76.6%, respectively. The docking and molecular dynamics simulation analyses indicated that girinimbine exhibited a higher binding affinity to AChE compared to propidium and tacrine. This finding was further confirmed by the docking, root mean square deviation (RMSD), root mean square fluctuation (RMSF), and radius of rotation analyses. In conclusion, M. koenigii girinimbine shows promise as an acetylcholinesterase inhibitor for Alzheimer’s disease. Further research, including in vivo studies and clinical trials, is needed to explore its potential as a plant-based drug candidate for AD treatment.